Methylation profiling: a diagnostic tool for the diagnosis of Merkel cell carcinoma of the lymph node without detectable skin primary tumor - Chantreau, Paul-Louis; Sohier, Pierre; Samimi, Mahtab; Tallegas, Matthias; Tallet, Anne; Guyetant, Serge; Goeppert, Benjamin; Al-Hussaini, Maysa; Toberer, Ferdinand; Giese, Nathalia; Rössler, Stephanie; Deimling, Andreas von; et al. (Virchows Archiv, 2025)
Merkel cell carcinoma (MCC) is an aggressive tumor mostly related to Merkel cell polyomavirus genomic integration. MCC can present either as a primary cutaneous tumor or as a lymph node metastasis without a primary skin tumor (MCCWOPT). The distinction between MCCWOPT and lymph node metastases of non-cutaneous neuroendocrine carcinomas remains challenging. The present study aims to determine whether the methylation profile can distinguish MCCWOPT from lymph node metastases of extracutaneous neuroendocrine carcinomas. Methylation profiles of twenty MCCWOPT were compared to 23 cutaneous MCC, 37 small-cell lung carcinomas, 17 and 34 well-differentiated neuroendocrine tumors of the ileum and pancreas. Among the controls, cutaneous MCC cases formed a cluster distinct from other extracutaneous neuroendocrine tumors. MCCWOPT clustered together with cutaneous MCC cases. Methylation profiling represents a promising additional tool for the diagnosis of MCCWOPT.
Gesehen am 12.02.2026